Clinical opioids differentially induce co-internalization of μ- and δ-opioid receptors. Issue 1 (April 2018) - Bao, Fenghua; Li, Chang-Lin; Chen, Xu-Qiao; Lu, Ying-Jin; Bao, Lan; Zhang, Xu
Opioid receptors play an important role in mediating the spinal analgesia. The μ-opioid receptor is the major target of opioid drugs widely used in clinics. However, the regulatory mechanisms of analgesic effect and tolerance for clinical μ-opioid receptor-targeting opioids remain to be fully investigated. Previous studies showed the interaction of δ-opioid receptor with μ-opioid receptor to form the μ-opioid receptor/δ-opioid receptor heteromers that could be processed in the degradation pathway after δ-opioid receptor agonist treatment. Here, we showed that clinical μ-opioid receptor-targeting opioids, morphine, fentanyl, and methadone, but not tramadol, caused μ-opioid receptor co-internalization with δ-opioid receptors in both transfected human embryonic kidney 293 cells and primary sensory neurons. Prolonged treatment of morphine led to μ-opioid receptor co-degradation with δ-opioid receptors. Furthermore, fentanyl and methadone, but not tramadol, induced the drug tolerance similar to morphine. Thus, the clinical μ-opioid receptor-targeting opioids including morphine, fentanyl, and methadone induce μ-opioid receptor co-internalization with δ-opioid receptors, which may be involved in the analgesic tolerance of these opioids.